An Improved Detection Algorithm of Three-phase Unbalanced Voltage Sag Detection Method for Improving Power Supply Reliability. Issue 4 (January 2021) - Peng, C; Hu, S L; Hao, X H
Abstract: With the popularization of high-power power electronic switching equipment and the technical update of electrical equipment, voltage sags have become a major problem affecting power quality, which seriously affects the reliability of power supply in power systems. In the case where the voltage sags failure cannot be avoided, rapid and accurate detection of the voltage sag has become a key technology for improving the reliability of the power supply of the power system. Based on the symmetrical component method, an improved detection algorithm for three-phase unbalanced voltage sag is proposed in this paper, which can significantly improve the detection speed and the reliability of power supply. The method firstly constructs the virtual orthogonal signal of the grid voltage and uses the symmetric component method to realize the fast and accurate extraction of the positive and negative sequence components of the grid voltage fundamental. In addition, an improved method for constructing virtual orthogonal signals is proposed in this paper, which effectively improves the accuracy of the constructed orthogonal signals. Finally, the feasibility and priority of the improved detection method have been verified by MATLAB/Simulink.